Climate-smart agriculture options in mixed crop-livestock systems in Africa south of the Sahara - Thornton, Philip K.; Rosenstock, Todd S.; Lamanna, Christine; Bell, P.; Förch, Wiebke; Henderson, Benjamin B.; Herrero, Mario (International Food Policy Research Institute, 2017)
Insurance programs have become an increasingly popular method for providing support to agricultural producers.1 Mahul and Stutley (2010) reported that in 2007 more than 100 countries had agricultural insurance programs available. In the United States multiple-peril crop insurance was available on a limited basis as early as the late 1930s; more recently, insurance has become the dominant safety-net program in the United States in terms of government outlays, overshadowing more traditional price and income support programs (Glauber 2012). Recent reforms in the European Community (EC) could potentially expand insurance programs there as well (European Commission 2013).